FAO species catalogue : - Whitehead, Peter J. P. (United Nations Development Programme, 1988)
The present volume includes comprising 4 families, 82 genera and some 355 species, contributing to more than a quarter of the world fish catch. It comprises an introductory section with general remarks on the systematics, habitat and fisheries of the family, a glossary of technical terms used, illustrated keys to genera and species, and detailed accounts on all species. Species accounts include drawing, scientific and vernacular names, information on habitat, biology and fisheries, and a distribution map.